2023
DOI: 10.1039/d3ra01478a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of SA/P(U-AM-ChCl) composite hydrogels by frontal polymerization and its performance study

Abstract: In this paper, we prepare SA/P(U-AM-ChCl) composite hydrogels with good self-healing properties through frontal polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Recently, Li et al [67] demonstrated the suitability of frontally polymerized deep eutectic monomers for obtaining poly(urea-co-acrylamide-co-choline chloride) hydrogels containing sodium alginate as a filler (from 0.5 to 8.0 wt.% loading). The effects of sodium alginate on the front velocities and temperatures as well as the mechanical, swelling, and self-healing features of the resulting hydrogels were thoroughly investigated.…”
Section: Figure 17mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Li et al [67] demonstrated the suitability of frontally polymerized deep eutectic monomers for obtaining poly(urea-co-acrylamide-co-choline chloride) hydrogels containing sodium alginate as a filler (from 0.5 to 8.0 wt.% loading). The effects of sodium alginate on the front velocities and temperatures as well as the mechanical, swelling, and self-healing features of the resulting hydrogels were thoroughly investigated.…”
Section: Figure 17mentioning
confidence: 99%
“…Moreover, the presence of β-cyclodextrins provided the hydrogels with interesting self-healing properties, with an efficiency approaching 92% for the systems containing the highest filler loading after 48 h (Figure 21). Recently, Li et al [67] demonstrated the suitability of frontally polymerized deep eutectic monomers for obtaining poly(urea-co-acrylamide-co-choline chloride) hydrogels containing sodium alginate as a filler (from 0.5 to 8.0 wt.% loading). The effects of sodium alginate on the front velocities and temperatures as well as the mechanical, swelling, and self-healing features of the resulting hydrogels were thoroughly investigated.…”
Section: Figure 17mentioning
confidence: 99%
“…Recently, Li et al [59] demonstrated the suitability of frontally polymerized deep eutectic monomers for obtaining poly(urea-co-acrylamide-co-choline chloride) hydrogels containing sodium alginate as a filler (from 0.5 to 8.0 wt.% loading). The effect of sodium alginate on the front velocities and temperatures, as well as on the mechanical, swelling, and self-healing features of the resulting hydrogels was thoroughly investigated.…”
Section: Self-healingmentioning
confidence: 99%